Amyopathic Dermatomyositis Manifesting With Marked Unilateral Eyelid Swelling and Hyperpigmentation in a Darker Skin Tone - Julia Goupil; Appledene Osbourne; Lucy Shi (Annals of Internal Medicine: Clinical Cases)
A 56-year-old man presented to the emergency department with unilateral eyelid swelling, a hyperpigmented rash, and no myositis. His physical examination showcases the variable presentation of classic dermatomyositis skin manifestations in darker skin. Dermatomyositis is an uncommon disease characterized by proximal muscle weakness and classic dermatologic manifestations. In amyopathic disease, the diagnosis relies on the identification of dermatologic findings, in which variation in manifestations can lead to delays in diagnosis and increased health disparities.